Research Ethics in the Digital Age Ethics for the Social Sciences and Humanities in Times of Mediatization and Digitization (Springer Fachmedien Wiesbaden : VS, 2018)
The book discusses the multiple issues of a digital research ethic in its interdisciplinary diversity. Digitization and mediatization alter social behavior and cultural traditions, thereby generating new objects of study and new research questions for the social sciences and humanities. Furthermore, mediatization and digitization increase the data volume and accessibility of (quantitative) research and proliferate methodological opportunities for scientific analyses. Hence, they profoundly affect research practices in multiple ways. While consequences concerning the subjects, objects, and addressees of research in the social sciences and humanities have rarely been reflected upon, this reflection lies at the center of the book. Contents Keynotes as to Core Issues Developing Research Standards in a Digitalized World Digital Publishing Applying Research Ethics to Different Digital Environments Target Groups Academics and scientists in the fields of communication studies, sociology and education Editors Farina Madita Dobrick and Jana Fischer are researchers at the Institute of Communication Studies at Technische Universität Dresden, Germany. Prof. Dr. Lutz Hagen is Director of the Institute for Communication Studies and Director of ZMS at Technische Universität Dresden, Germany.